2020
DOI: 10.3390/antiox9060477
|View full text |Cite
|
Sign up to set email alerts
|

Use of Melatonin in Oxidative Stress Related Neonatal Diseases

Abstract: Reactive oxygen species have a crucial role in the pathogenesis of perinatal diseases. Exposure to inflammation, infections, or high oxygen concentrations is frequent in preterm infants, who have high free iron levels that enhance toxic radical generation and diminish antioxidant defense. The peculiar susceptibility of newborns to oxidative stress supports the prophylactic use of melatonin in preventing or decreasing oxidative stress-mediated diseases. Melatonin, an effective direct free-radical scavenger, eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 87 publications
2
40
0
1
Order By: Relevance
“…Oxidative stress is an imbalance between oxidants and antioxidants. It is mainly caused by ROS and could lead to cellular damage [41]. Accumulation of cellular oxidative damage leads to various diseases such as inflammation, cardiovascular diseases, diabetes, obesity, and abnormal aging [13].…”
Section: Protective Effect Of Emc Against Aaph-stimulated Oxidative Smentioning
confidence: 99%
“…Oxidative stress is an imbalance between oxidants and antioxidants. It is mainly caused by ROS and could lead to cellular damage [41]. Accumulation of cellular oxidative damage leads to various diseases such as inflammation, cardiovascular diseases, diabetes, obesity, and abnormal aging [13].…”
Section: Protective Effect Of Emc Against Aaph-stimulated Oxidative Smentioning
confidence: 99%
“…Once synthesized, melatonin is released into the blood. Previous studies have shown that melatonin can demonstrate significant immune regulation, anti-tumor, and anti-aging effects and provides protective effects on the brain, heart, liver and other important organs[ 9 ]. Plasma melatonin was reported to be associated with the risk of several diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MT was first found in 1958 in animal as an important neurohormone; then it has been reported to regulate a series of biological activities including sleep‐wake cycles, mood, sexual behavior, circadian rhythms, and anti‐oxidative activities 8‐10 . MT in plants was initially detected in land plants in 1995 11 . According to the European Community Legislation, MT has been classified by the European Chemical Agency (ECHA) as one non‐hazardous substance for use as plant protector and/or biostimulant 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the investigated aspects, the protective action of MT against biotic and abiotic stresses has been researched extensively in plants 11 . MT exerts the protective action by acting as one direct ROS scavenging molecule (a single MT molecule can scavenge up to 10 ROSs) and activating a series of downstream stress‐responsive genes 17‐19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation